Biomass of fine roots in agroforestry arrangements with cocoa in the western Colombian Amazon - Rico A., Adrián; Suárez S., Juan Carlos (Revista de Ciencias Agrícolas, 2018)
The agroforestry arrangements with cocoa have a diversified structure, which influences the behavior of fine roots, whose distribution is influenced by different cultural practices. The objective of the present work was to study the distribution, the contribution of biomass of fine roots in relation to the apparent density and the percentage of humidity in agroforestry arrangements with cocoa in the CIMAZ Macagual Research Center (1°37'LN and 75°36'LW). The sampling was developed in three agroforestry arrangements with cocoa classified in intense shade, semi-shade and full sun. For the extraction of the biomass of roots the cylinder of known volume was used every 10cm until reaching 1m of depth. The fine roots were extracted through a mesh size <2mm. There were significant statistical differences between the array-depth interaction for the variable root biomass (<0.001) with a positive correlation (0.26) between weight and bulk density. The highest accumulation of root biomass occurred between the first 20 cm of depth in the three systems studied, where the apparent density increases in the different soil profiles; in turn, the gravimetric humidity was greater in the agroforestry arrangements than in cocoa in full sun, showing significant differences (P<0.001) with a negative correlation (-0.75) in terms of the depths. In this sense, agroforestry systems favor the availability of water in the first soil profiles, increasing the presence of fine roots.